2000
DOI: 10.1063/1.1290124
|View full text |Cite
|
Sign up to set email alerts
|

A new method of calculation of Franck–Condon factors which includes allowance for anharmonicity and the Duschinsky effect: Simulation of the He I photoelectron spectrum of ClO2

Abstract: A new method of Franck-Condon ͑FC͒ factor calculation for nonlinear polyatomics, which includes anharmonicity and Duschinsky rotation, is reported. Watson's Hamiltonian is employed in this method with multidimensional ab initio potential energy functions. The anharmonic vibrational wave functions are expressed as linear combinations of the products of harmonic oscillator functions. The Duschinsky effect, which arises from the rotation of the normal modes of the two electronic states involved in the electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 106 publications
(43 citation statements)
references
References 49 publications
1
42
0
Order By: Relevance
“…33 It shall be noted here that Duschinsky effects have also been accounted for by other authors within the determination of Franck-Condon factors in many anharmonic calculations for triatomic systems, but also for more extended systems. 34 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 which led to a sum of FCFs being larger than 0.9999. From these the most important have been selected, which were subsequently computed by state-specific configuration-selective VCI calculations with configuration spaces including quadruple excitations and accounting for vibrational angular momentum terms.…”
Section: Computational Detailsmentioning
confidence: 87%
“…33 It shall be noted here that Duschinsky effects have also been accounted for by other authors within the determination of Franck-Condon factors in many anharmonic calculations for triatomic systems, but also for more extended systems. 34 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 which led to a sum of FCFs being larger than 0.9999. From these the most important have been selected, which were subsequently computed by state-specific configuration-selective VCI calculations with configuration spaces including quadruple excitations and accounting for vibrational angular momentum terms.…”
Section: Computational Detailsmentioning
confidence: 87%
“…Botschwina et al [15] are one of the few research groups performing anharmonic FCF calculations in this way. Recently, details of a few other types of anharmonic FCF methods have been published [12][13][14][16][17][18]. Franck-Condon factor calculations that consider anharmonicity effects will be the focus of our future work.…”
Section: Resultsmentioning
confidence: 99%
“…Geometry optimization and harmonic vibrational frequency calculations were carried out on theX 2 [8,[10][11][12][13][14] was also carried out.…”
Section: Computational Detailsmentioning
confidence: 99%
“…With quantum chemical computing programs being readily available, geometries and normal modes of small to medium size molecules in different electronic states can now be calculated routinely. Based on these methods, numerous applications of FC calculations have been presented in the literature [1][2][3][4][5][6][7][8][9][10][11][12][13][14], and most of these studies just focus on the interpretation of experimentally known spectra. Because the geometry difference between two electronic states is a major factor that influences FC intensities, the simulation of vibronic spectra of ployatomic molecules can be regarded as a valuable test with respect to the quality of calculated geometries and as a starting point to obtain improved structures.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, spectral simulations of vibrational structure based on computed Franck-Condon factors (FCF) could provide fingerprint type identification of an observed spectrum, in terms of both the carrier and the electronic states in the transition (see, for examples, [9,10], and references therein). Also, it has been demonstrated that spectral simulations can be very useful in establishing vibrational assignments in an electronic spectrum observed with complex vibrational structure [1][2][3][4][5]7,10,11].…”
Section: Introductionmentioning
confidence: 99%